PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS VIDEO ANIMASI TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DENGAN MENGGUNAKAN KINEMASTER - Suri, Indah Resti Ayuni; Mujib, Mujib; Lusiana, Lusiana (Faculty of Teacher Training and Education, 2024)
Learning media is a means to facilitate learning process activities, especially mathematics learning. This research aims to develop animated video-based mathematics learning media using Kinemaster, then find out its attractiveness and influence on the ability to understand mathematical concepts. This research and development uses the research and development (R&D) method with the ADDIE development model, namely Analysis, Design , Development , Implementation, and Evaluation . Data collection techniques using questionnaires and tests. This learning media was declared valid based on validators with a score of 81%, which means it is very valid. For understanding the concept, students received an average score of 61% in the good category. The attractiveness of the animated video can be seen based on the questionnaire given to students. the teacher response questionnaire received a score of 84.5% (very good), and the student response questionnaire obtained a score of 75% (good). Animation video-based learning media is suitable for use and can be used as a learning resource.